Co-sleeping versus sleep training: publications with advice for parents (2017)
Introduction: Sleep patterns in infants is one of the main issues regarding children upbringing and has different positions in publications.Objective: To analyze 63 publications with parenting advice on sleep in infants to subsequently characterize them in terms of their position on co-sleeping and sleep training.Materials and methods: Publications issued in the past two decades, available for purchase and/or reference in Chile. 63 publications, including parenting advice books and 32 web sites, were identified.Results: 65% of the analyzed publications favored some form co-sleeping; 76% mentioned sleep training, expressing a tendency to defend and/or accept the strategy known as ‘positive routines’ rather than ‘cry it out methods’.Conclusions: Chilean parents are confronted with contradictory information. The current debate on the regulation of infant sleep is also seen in Ibero-America, although expert opinion differs from that found in Anglo-Saxon samples.